2016
DOI: 10.1088/2043-6262/7/1/015003
|View full text |Cite
|
Sign up to set email alerts
|

Progress in the research and development of photonic structure devices

Abstract: In this paper we review the results of the research and development of photonic structure devices performed in the Institute of Materials Science in the period from 2010–2015. We have developed a configuration of 1D photonic crystal (PC) microcavities based on porous silicon (PS) layers and applied them to optical sensing devices that can be used for the determination of organic content with a very low concentration in different liquid environments. Various important scientific and technological applications o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 45 publications
(80 reference statements)
0
5
0
Order By: Relevance
“…There were various research groups working on flexible and bilayer memristors. [ 33–43 ] A study for comparing the present flexible memristor with other related reported works is carried out, the present BL flexible device exhibits gradual switching, superior data retention, shorter pulse width, higher endurance with small bending radius, more number of conductance states and pattern recognition for the synaptic applications. The characteristics of this work in comparison with those of previous works are presented in Table 1 .…”
Section: Introductionmentioning
confidence: 99%
“…There were various research groups working on flexible and bilayer memristors. [ 33–43 ] A study for comparing the present flexible memristor with other related reported works is carried out, the present BL flexible device exhibits gradual switching, superior data retention, shorter pulse width, higher endurance with small bending radius, more number of conductance states and pattern recognition for the synaptic applications. The characteristics of this work in comparison with those of previous works are presented in Table 1 .…”
Section: Introductionmentioning
confidence: 99%
“…Also, V. Pham et al . developed a 1DPC microcavity sensor based on PSi multilayers 31 . The 1DPC sensor showed a sensitivity of about 200 nm/RIU, and it can be used for the determination of organic content in different liquid solutions.…”
Section: Introductionmentioning
confidence: 99%
“…6(b) depicts the PL behavior of the fabricated s-SWNTs. It is seen that the obtained solution contains only semiconducting type with the chirality of (8,6) and (8,7) [44]. In addition, the PL emission happens around 1280 nm for the (8,7) chirality s-SWNTs which matches well with the resonance wavelength of the cavity.…”
Section: Photoluminescence Enhancement Of S-swnts In Slotted Silmentioning
confidence: 52%
“…In group IV silicon photonics, photonic crystal (PhC) structures [4][5][6] have been widely exploited in order to take the benefit from slow-light mode in such a periodic modulation geometry of the refractive index [7]. With the band gaps from dielectric lattices, PhCs are of great interest for applications in optical sensors [8], multi/demultiplexers [9], quantum information processing [10]. These structures including 1-dimensional (1D), 2-dimensional (2D) and 3-dimensional (3D) PhC have been designed and fabricated in which the width of the band gap can be manipulated by the modulation geometric parameters, e.g.…”
Section: Introductionmentioning
confidence: 99%